IMPLEMENTASI MEDIA FLASH CARD UNTUK MENINGKATKAN PENGUASAAN VOCABULARY SISWA KELAS V SD NEGERI 173530 TANGGA BATU - Sembiring, Friscilla; Sembiring, Margaretta Br. (Jurnal Curere, 2025)
This research is motivated by the low mastery of Vocabulary of Class V students of SD Negeri 173530 Tangga Batu, where teachers still apply the lecture method in learning English and students do not achieve the KKM score. This study aims to improve the mastery of English vocabulary on the material of objects in the classroom by using pictures in class V students of SD Negeri 173530 Tangga Batu. The vocabulary mastery referred to in this study is reading vocabulary using Flashcard media, writing vocabulary and interpreting vocabulary. The subjects in this study were 30 class V students of SD Negeri 173530 Tangga Batu. The method used is the Classroom Action Research method with a research design according to Kemmis and Mc Taggart. The data collection methods used are tests, performance, observation and field notes. The instruments used are student and teacher observation sheets, short answer sheets and field note sheets. The data analysis technique used is quantitative descriptive. The results of the study in cycle I showed students' ability to interpret English vocabulary on the material of objects in the classroom.